2019
DOI: 10.1523/jneurosci.1427-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation Augments Spike Sequence Replay and Memory Consolidation during Slow-Wave Sleep

Abstract: Newly acquired memory traces are spontaneously reactivated during slow-wave sleep (SWS), leading to the consolidation of recent memories. Empirical studies found that sensory stimulation during SWS can selectively enhance memory consolidation with the effect depending on the phase of stimulation. In this new study, we aimed to understand the mechanisms behind the role of sensory stimulation on memory consolidation using computational models implementing effects of neuromodulators to simulate transitions betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 55 publications
2
21
1
Order By: Relevance
“…Similarly, spatial memory consolidation has been shown to improve following cued reactivation of memory traces during NREM sleep ( Paller and Voss, 2004 ; Oudiette et al, 2013 ; Oudiette and Paller, 2013 ; Papalambros et al, 2017 ). Our recent computational studies found that sleep dynamics can lead to replay and strengthening of recently learned memory traces ( Wei et al, 2016 ; Wei et al, 2018 ; Wei et al, 2020 ). These studies point to the critical role of sleep in memory consolidation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, spatial memory consolidation has been shown to improve following cued reactivation of memory traces during NREM sleep ( Paller and Voss, 2004 ; Oudiette et al, 2013 ; Oudiette and Paller, 2013 ; Papalambros et al, 2017 ). Our recent computational studies found that sleep dynamics can lead to replay and strengthening of recently learned memory traces ( Wei et al, 2016 ; Wei et al, 2018 ; Wei et al, 2020 ). These studies point to the critical role of sleep in memory consolidation.…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al [ 26 , 47 , 48 ] tested several ways of closed-loop stimulation, including the protocol of Ngo et al [ 3 ], in a cellular level model. Their results showed that the correct spatio-temporal localization of stimuli could facilitate the replay of a cortical sequence associated with the stimulation site, pointing to the need for peaks nesting for strengthening the neural connections.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach to improving the stimulation paradigm that attempts to increase SP and SO events during SWS is the use of mathematical models of brain activity [ 25 , 26 ]. In this way, mechanistic insights about the generation of SP and SO activity can guide the search for a better stimulation that maximizes its efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…We, as well as other investigators, suggest that deviant study outcomes should be taken as important indicators for interactions between undisclosed overt and covert confounding factors. Such confounding factors that can affect neural responses and memory consolidation are the precise phase of sensory stimulation relative to the endogenous coupling of rhythms (Wei et al, 2020;Weigenand et al, 2016), a different length in time Figure 2: Potential levels of interaction during neural processing in sleep. The square boxes indicate learning and recall performance on three tasks: motivated forgetting (top), object-place recognition task (bottom left), and figural paired associate task (bottom right).…”
Section: Memory Consolidationrecent Neuromodulatory Approaches and Rementioning
confidence: 99%